The Relationship between Health Service Quality and Patient Satisfaction at the Labanan Health Center, Teluk Bayur District Berau District - Sutoyo, Irwan; Rusdi, Rusdi (Universitas Muhammadiyah Kalimantan Timur, 2023)
One significant effort to increase Indonesia's health sector competitiveness is to improve health services' quality. Efforts to improve the quality of health services are challenging because health services are carried out starting from the sub-health center, main health center, and hospital. These health facilities must provide full service to patients to feel well served. This study aimed to analyze the relationship between the quality of health services and patient satisfaction at the Labanan Health Center, Teluk Bayur District, Berau Regency. This research method uses a quantitative descriptive-analytic approach with a correlational type of research. The data analysis technique uses the chi-square statistic test. This research was conducted at the Labanan Health Center, Teluk Bayur District, Berau Regency, with a total sample of 124 respondents. The study results showed that 46 respondents (63.9%) stated that the service quality was excellent and satisfied with the services at the Labanan Health Center. In comparison, 23 respondents (44.2%) stated that the service quality was excellent and dissatisfied. Meanwhile, 26 respondents (36.1%) noted that the quality of service was not good. Still, they were satisfied with the quality of service at the Labanan Health Center. Twenty-nine respondents (55.8%) said the service quality was not good. From the results of statistical tests (p-value = 0.046 <0.05).